M7: An efficient size-resolved aerosol microphysics module for large-scale aerosol transport models - Vignati, E; Wilson, J; Stier, P (2004)
An aerosol model (M7) designed to be coupled to general circulation models (GCM) and chemistry transport models (CTM) is described. In M7 the aerosol population is divided into two types of particles: mixed, or water-soluble particles, and insoluble particles. The particles are represented by seven classes, using a "pseudomodal" approach. Four classes are for the mixed particles representing nucleation, Aitken, accumulation, and coarse mode, and three are for the insoluble (Aitken, accumulation, and coarse mode). The components considered are mineral dust, black carbon (BC) and primary organic carbon (OC), sulfate, and sea salt. The aerosol dynamic processes in M7 include nucleation, coagulation, and condensation of sulfuric acid. Mixed particles are formed from insoluble particles by coagulation and condensation. The integration scheme is computationally very efficient. The model has been tested against the analytical solution and a sectional model for the formation of SO4/BC mixed particles, evaluating the mixing by condensation and coagulation. Furthermore, M7 has been run in free tropospheric conditions and compared to aircraft observations. M7 has proven to be accurate and fast enough to be included in a GCM or CTM. Copyright 2004 by the American Geophysical Union.